(untitled) (MAUSAM, 1961)
It is well known that there are very strong upward and downward currents in a thunder-storm. The observations are based mostly on the occurrence of hail and the experiences of pilots who have occasionally ventured into them. While a few downward and upward motions of sounding balloons have been observed, and reported, it has not been possi-ble to state definitely whether the observed downward motion of the balloon observed from the record is due to the vertical currents or due to the accumulation of snow or due to the heavy rain experienced by the balloon.